Analisis Penggunaan Layanan M-Banking Dalam Mendukung Transaksi Keuangan Pada Mahasiswa - Diar Muzna Tangke; Musriha , Hedi; Huwae, Filiyan (Publikasi Inspirasi Indonesia, 2024)
Banking services and facilities are the key to attracting potential and existing customers to remain loyal. One of the banking facilities available is mobile banking or M-Banking. Students are one of the potential markets for mobile banking which takes advantage of developments in information technology. The aim of this research is to analyze the use of mobile banking services to support financial transactions among students with a sample size of 60 students who use mobile banking. The research uses quantitative methods. The research results show that the ease of use variable, the benefits variable and the design quality variable have a positive and significant effect on the use of mobile banking. Meanwhile, the trust variable has a positive and insignificant effect on the use of mobile banking among students.